Penerapan Kompres Dingin terhadap Nyeri Luka Perineum pada Ibu Post Partum di RS PKU Muhammadiyah Karanganyar - Nina Karnila; Tri Susilowati (Vitalitas Medis : Jurnal Kesehatan dan Kedokteran, 2024)
Background: Based on world data, there have been 2.7 million cases of perineal rupture in mothers giving birth. This figure is estimated to reach the highest number collected until 2050, which is 6.3 million. Perineal rupture in Asia also often occurs in society, which is around 50%. According to data from the Indonesian Demographic Health Survey (SDKI), 75% of mothers who give birth in Indonesia experience perineal tears or perineal rupture. Objective: To describe the results of measuring the pain scale using the cold compress method. Method: This study method uses a case study method with a descriptive design and uses a Numeric Rating Scale (NRS) pain measurement sheet, in the cold compress method, the variable measured is perineal wound pain that has been given intervention 3 times a day in a span of 5-10 minutes for 3 days. Results: After cold compresses were given to two respondents who experienced perineal wounds, there was a change in the pain scale which was included in the mild pain category. Conclusion: The application of cold compresses can reduce the scale of perineal wound pain in postpartum patients.